PENERAPAN ASUHAN KEPERAWATAN PADA PASIEN TN. I DENGAN TUBERKULOSIS PARU DALAM PEMENUHAN KEBUTUHAN OKSIGENASI DI RUANGAN BAJI ATI RUMAH SAKIT UMUM DAERAH LABUANG BAJI MAKASSAR - Nurlina Nurlina (Jurusan Keperawatan Poltekkes Kemenkes Makassar, 2019)
ABSTRACT Background: Tuberculosis (TB) is still a major health problem in the world, almost one third of the world's population is infected with TB, 95% of the world's TB death occurs in middle and low-income countries. The prevalence of the population of Indonesia in the diagnosis of pulmonary TB of health workers in 2013 is 0.4 percent. Based on the characteristic of the population, the prevalence of pulmonary tuberculosis tends to increase with age, in low education, and not work. Purpose: To know the application of nursing care to the patient. I with pulmonary tuberculosis in the fulfillment of oxygenation requirements. Methods were performed: descriptive and using techniques Observation method and interview method with one resource (Patient) Pulmonary Tuberculosis. Results: The results showed that ineffective airway ineffectiveness not resolved marked with the client still appears coughing. And inefectiveness of the pattern of breath has been resolved is marked with the client is not crowded again, kliem seems not overcrowded, breathing: 24 x/i. Conclusion:After the research can be concluded that by doing nursing care in oxygenation needs, need to pay attention to patient of airway and breathing pattern. Suggestion: to nurse to maintain therapeutic communication techniques, so that they can maintain a relationship of mutual trust to patients and families of patients.